Consumer Perception on Digital Marketing of Fisheries Product in Lamongan, East Java, Indonesia - M. Khairul Anam; Muntalim Muntalim; Faisol Mas'ud (Jurnal Analisis Bisnis Ekonomi, 2023)
Digital marketing has recently become a serious concern for economic actors. Consumer perceptions and behavior towards digital marketing of fishery products are very important to determine marketing strategies and market segmentation. This study aims to analyze consumer perceptions and satisfaction of online fishery products using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). This study used accidental sampling with 135 respondents. The results showed that product quality, price, discount availability, delivery time, packaging, security, and COD (Cash on Delivery) system had high performance values. While shipping costs have low performance. While the results of consumer satisfaction show that the CSI score is 62.4%, meaning that consumers are satisfied with the online fishery product sales service. However, business actors need to maintain and improve their service performance